2023
DOI: 10.1093/plcell/koad204
|View full text |Cite
|
Sign up to set email alerts
|

Allelic compatibility in plant immune receptors facilitates engineering of new effector recognition specificities

Abstract: Engineering the plant immune system offers genetic solutions to mitigate crop diseases caused by diverse agriculturally significant pathogens and pests. Modification of intracellular plant immune receptors of the nucleotide-binding leucine rich repeat (NLR) superfamily for expanded recognition of pathogen virulence proteins (effectors) is a promising approach for engineering disease resistance. However, engineering can cause NLR autoactivation, resulting in constitutive defence responses that are deleterious t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The NLR-ID gene has become a key target for NLR engineering due to its ability to recognize various pathogen effectors via their varying IDs. While the HMA domain represents the model ID in plant immunity [ 82 , 83 ] and has been engineered to mediate broad pathogen resistance [ 84 , 85 , 86 ], the mining and detailed analysis of other IDs in atypical NLR proteins could help us to design more specialized NLRs to cope with rapidly evolving pathogens. Therefore, our study provides a toolkit for the functional study of the IDs in plant NLR proteins, and the broad-spectrum antiviral gene SRZ4 reported here might have significant application value.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR-ID gene has become a key target for NLR engineering due to its ability to recognize various pathogen effectors via their varying IDs. While the HMA domain represents the model ID in plant immunity [ 82 , 83 ] and has been engineered to mediate broad pathogen resistance [ 84 , 85 , 86 ], the mining and detailed analysis of other IDs in atypical NLR proteins could help us to design more specialized NLRs to cope with rapidly evolving pathogens. Therefore, our study provides a toolkit for the functional study of the IDs in plant NLR proteins, and the broad-spectrum antiviral gene SRZ4 reported here might have significant application value.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death phenotypes were scored with a range from 0 (no visible necrosis) to 7 (fully confluent necrosis) according to Adachi et al, 2019a). Quantification and statistical analysis was performed by using the besthr R library (MacLean, 2019) and plotted using a script described in Bentham et al, 2023. Scoring for all experiments can be found in Supplementary Dataset 4.…”
Section: Methodsmentioning
confidence: 99%
“…Structure-guided bioengineering of the effector-binding regions of NLRs is a promising mechanism to modify receptor recognition specificity (4)(5)(6)(7)(8). Editing or domain-swapping of non-canonical integrated domains found in some NLRs has been particularly effective for either expanding or altering the effector response profiles of these immune receptors (4,7,(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The RGA5-HMA domain has been engineered to gain binding to non-corresponding MAX effectors including AVR-PikD and AVR-Pib (4,9,12,13). Importantly, to achieve full resistance to AVR-Pib in cereals, the engineered full-length RGA5/RGA4 receptor pair required additional modification of the C-terminal region that directly follows the HMA domain in the RGA5 receptor (12,13).…”
Section: Introductionmentioning
confidence: 99%